Zirconium-based MOF material, preparation method thereof and preparation method of 5-hydroxymethylfurfural

By using zirconium-based MOF materials as catalysts and reacting under a specific solvent system, the problems of many by-products and low yields in the preparation of 5-hydroxymethylfurfural in the prior art are solved, and an efficient and green catalytic effect is achieved.

CN119859277APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311369884.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the preparation of 5-hydroxymethylfurfural, the prior art has problems such as many by-products, low yields, high toxicity of the catalyst and difficult to recover, making it difficult to achieve green production.

Method used

Zirconium-based MOF material is used as the catalyst. The contact angle between the material and water is not less than 50°, and contains no less than 1.0% by weight of sulfonic acid-based modified groups. It is reacted under an alcohol solvent and a non-alcohol organic solvent system to avoid the problem of unstable structure of the MOF material in water.

Benefits of technology

The conversion efficiency of fructose and the yield of 5-hydroxymethylfurfural are improved, the generation of by-products is reduced, and the recycling and utilization rate of catalysts is also improved, achieving the goal of green production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859277A_ABST
    Figure CN119859277A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysis, in particular to a zirconium-based MOF material and a preparation method thereof and a preparation method of 5-hydroxymethylfurfural. The contact angle between the zirconium-based MOF material and water is not less than 50 degrees, and the zirconium-based MOF material contains not less than 1.0 wt% of sulfonic acid group modified groups. The contact angle between the zirconium-based MOF material and water is not less than 50 degrees, and the zirconium-based MOF material contains not less than 1.0 wt% of sulfonic acid group modified groups, so that the zirconium-based MOF material has unique acid properties, and is especially suitable for being applied to biomass dehydration reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysis, and in particular to a zirconium-based MOF material and a preparation method thereof, and a preparation method of 5-hydroxymethylfurfural. Background Art

[0002] With the over-exploitation and utilization of fossil fuels, the world is facing a severe energy crisis and environmental pollution. Biomass has the advantages of sustainability and wide sources, and the research on using it as raw material to synthesize energy and fine chemicals has become a hot topic in the field of biomass utilization.

[0003] 5-Hydroxymethylfurfural (HMF) is one of the important platform compounds released by the U.S. Department of Energy and plays an important role in the field of biomass energy. HMF molecules contain highly active furan rings, hydroxymethyl and aldehyde groups, which can be further transformed through hydrogenation, oxidative dehydrogenation, esterification, halogenation, polymerization, hydrolysis and other processes to synthesize a series of products with large markets and high added value. It is a monomer for the production of polymers and can also be used as a raw material to synthesize drug intermediates, antifungal agents, macrocyclic ligands and liquid fuels. Therefore, it is known as an important bridge compound connecting biomass chemical industry and petrochemical industry, and its synthesis has attracted extensive attention from researchers at home and abroad.

[0004] Acidic catalysts are commonly used catalysts for fructose dehydration to produce HMF, including inorganic acids, inorganic salts and solid acids. Soluble inorganic acids are the cheapest acid catalysts, which often catalyze fructose dehydration in aqueous solution and have high catalytic activity, but the generation of formic acid, levulinic acid and humin during the reaction is very serious. CN113234043A reports a preparation and separation method for 5-hydroxymethylfurfural prepared by fructose dehydration, using p-toluenesulfonic acid, hydrochloric acid and the like as catalysts, although the reaction cost is reduced, there are problems such as difficult product separation, severe equipment corrosion and environmental pollution.

[0005] Solid acid has the advantages of no corrosion to equipment, little pollution, and easy separation. CN103028424A reports a preparation method of a solid acid catalyst for the synthesis of 5-hydroxymethylfurfural, wherein the oxide is dissolved in deionized water, and a precipitant is used to precipitate it completely, and after aging, the precipitate is washed, filtered, and dried, and then the precipitate is immersed in a sulfuric acid solution or a chromium solution. After impregnation, the solid acid catalyst is roasted to obtain a solid acid catalyst for the synthesis of 5-hydroxymethylfurfural with a high yield. However, since the main active components of the catalyst are sulfate and chromium ions, a certain burden is imposed on the environment. CN101812039A provides a method for generating 5-hydroxymethylfurfural by catalysis of an ionic liquid, and the reaction belongs to a homogeneous catalytic reaction, with a small amount of catalyst added and a high yield. However, the reaction steps are cumbersome, and processes such as distillation are required. The selection of anions and cations of the ionic liquid catalyst is complicated, and organic reagents also bring a certain burden to the environment.

[0006] In summary, the existing methods for preparing 5-hydroxymethylfurfural have many by-products, low yield, high catalyst toxicity and difficulty in recovery. Therefore, it is necessary to find a suitable reaction system to improve the yield of 5-hydroxymethylfurfural, reduce the generation of by-products, and improve the recovery rate of the catalyst to meet the needs of green production. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem that the catalytic system and MOF materials in the prior art are not suitable for the conversion reaction of biomass, especially fructose, and to provide a zirconium-based MOF material and a preparation method thereof and a preparation method of 5-hydroxymethylfurfural. The zirconium-based MOF material has the advantages of high fructose conversion efficiency and high product selectivity.

[0008] The inventors found that most existing MOF materials are hydrophilic materials, and their skeletons are prone to collapse in aqueous solutions. In the process of biomass catalytic conversion, many hydrothermal reactions are involved, so many MOF materials are not suitable for use in the biomass conversion process. Some existing technologies use high-boiling point or highly toxic solvents such as dimethyl sulfoxide and 1,4-dioxane, which do not conform to the green environmental protection concept advocated by the development of biomass conversion.

[0009] In order to achieve the above object, the first aspect of the present invention provides a zirconium-based MOF material, wherein the contact angle between the zirconium-based MOF material and water is not less than 50°, and the zirconium-based MOF material contains not less than 1.0 wt% of sulfonic acid modified groups.

[0010] The second aspect of the present invention provides a method for preparing the zirconium-based MOF material according to the first aspect of the present invention, the preparation method comprising:

[0011] Step (1), preparing UiO-66-NH2;

[0012] Step (2), modifying UiO-66-NH2 with alkylbenzene sulfonic acid, separating after standing, and vacuum drying.

[0013] The third aspect of the present invention provides a method for preparing 5-hydroxymethylfurfural, which comprises: in an alcohol solvent and a non-alcohol organic solvent system, under an inert atmosphere, contacting fructose and a catalyst for reaction, and cooling; the catalyst comprises the zirconium-based MOF material described in the first aspect of the present invention.

[0014] Through the above technical solution, the present invention has the following advantages:

[0015] The contact angle between the zirconium-based MOF material of the present invention and water is not less than 50°, and the zirconium-based MOF material contains not less than 1.0 wt% of sulfonic acid modified groups, so that the zirconium-based MOF material has unique acid properties and is particularly suitable for use in biomass dehydration reactions.

[0016] The preparation method of 5-hydroxymethylfurfural of the present invention adopts a unique solvent system, utilizes the partial dissolution of fructose in alcohol solvents, and uses alcohol solvents instead of water to dissolve fructose, which can effectively avoid the MOF material from having a structural instability in water and a reduced catalytic performance, and fructose reacts while dissolving in alcohol solvents, which largely avoids the hydration and decomposition of HMF at high temperature to generate formic acid and levulinic acid. In addition, the solvent system has low toxicity and low boiling point, which is more conducive to the subsequent separation and purification of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a scanning electron microscope image (SEM) of UiO-66-NH2-SO3H in Example 1;

[0018] Figure 2 is the contact angle between UiO-66-NH2-SO3H and water in Example 1;

[0019] Figure 3 The product distribution in Example 7 using UiO-66-NH2-SO3H of Example 1 as the catalyst;

[0020] Figure 4 This is the product distribution of UiO-66-NH2 as the catalyst in Comparative Example 1. DETAILED DESCRIPTION

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] The present invention provides a zirconium-based MOF material, wherein the contact angle between the zirconium-based MOF material and water is not less than 50°, and the zirconium-based MOF material contains not less than 1.0 wt % of sulfonic acid modified groups.

[0023] The contact angle between the zirconium-based MOF material of the present invention and water is not less than 50°, and the zirconium-based MOF material contains not less than 1.0 wt % of sulfonic acid-modified groups, so that the zirconium-based MOF material has unique acid properties.

[0024] According to a preferred embodiment of the present invention, the contact angle between the zirconium-based MOF material and water is 50-120°, preferably 60-100°.

[0025] According to a preferred embodiment of the present invention, the content of the modified groups in the zirconium-based MOF material is 1.0-10.0 wt%, preferably 1.2-6.0 wt%.

[0026] According to a preferred embodiment of the present invention, the zirconium-based MOF material has a polyhedral cubic structure, and the size of the material is 50-800 nm, preferably 100-500 nm.

[0027] The present invention provides a method for preparing the zirconium-based MOF material, the preparation method comprising:

[0028] Step (1), preparing UiO-66-NH2;

[0029] Step (2), modifying UiO-66-NH2 with alkylbenzene sulfonic acid, separating after standing, and vacuum drying.

[0030] The zirconium-based MOF material having the aforementioned characteristics of the present invention can be prepared by the preparation method of the present invention.

[0031] According to a preferred embodiment of the present invention, the alkylbenzene sulfonic acid is a benzene sulfonic acid having a C10-C16 alkyl branch, preferably selected from dodecylbenzene sulfonic acid and / or hexadecylbenzene sulfonic acid.

[0032] According to a preferred embodiment of the present invention, step (1) comprises: dissolving zirconium salt and 2-aminoterephthalic acid in a first solvent to form solution A, adding a carboxylic acid compound to solution A to form solution B for crystallization reaction, and drying.

[0033] According to a preferred embodiment of the present invention, after the crystallization reaction and before drying, the mixture is cooled to room temperature, the mother liquor is removed, and the mixture is washed with ethanol several times.

[0034] In the present invention, there is no particular requirement for the method of adding the carboxylic acid compound. According to a preferred embodiment of the present invention, the carboxylic acid compound is added dropwise, preferably at a rate of 0.1-1 ml / min.

[0035] According to a preferred embodiment of the present invention, step (2) comprises: dissolving UiO-66-NH2 in a second solvent, adding alkylbenzene sulfonic acid for modification, standing and separating, repeating the modification, standing and separating steps at least once, preferably 1-3 times, and vacuum drying.

[0036] According to a preferred embodiment of the present invention, the separated material is washed before the vacuum drying, and preferably the washing agent is selected from toluene and / or ethanol, and more preferably washed 1-5 times.

[0037] In the present invention, the optional range of the first solvent is relatively wide. According to a preferred embodiment of the present invention, the first solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and triethylamine.

[0038] In the present invention, the optional range of the second solvent is relatively wide. According to a preferred embodiment of the present invention, the second solvent is selected from at least one of dichloromethane, toluene, tetrahydrofuran and p-xylene.

[0039] In the present invention, the zirconium salt may be a conventional choice in the art, for example, it may be at least one of zirconium tetrachloride, zirconium oxychloride, zirconium nitrate, and zirconium citrate.

[0040] In the present invention, the optional range of the carboxylic acid is relatively wide. According to a preferred embodiment of the present invention, the carboxylic acid compound includes at least one of formic acid, acetic acid, citric acid, tartaric acid, benzoic acid, salicylic acid, phthalic acid, phenylpropionic acid, phenylacetic acid, succinic acid, and p-nitrobenzoic acid.

[0041] In the present invention, in step (1), there is no special requirement for the molar ratio of the zirconium salt to 2-aminoterephthalic acid. According to a preferred embodiment of the present invention, the molar ratio of the zirconium salt to 2-aminoterephthalic acid is 1:(0.5-3).

[0042] In the present invention, in step (1), there is no special requirement for the usage ratio of the first solvent to the zirconium salt. According to a preferred embodiment of the present invention, the usage ratio of the first solvent to the zirconium salt is 5-100 mL solvent / 1.0 g zirconium salt.

[0043] In the present invention, in step (1), there is no special requirement for the usage ratio of the carboxylic acid compound to the zirconium salt. According to a preferred embodiment of the present invention, the usage ratio of the carboxylic acid compound to the zirconium salt is 0.01-20 mL of the carboxylic acid compound / 1.0 g of the zirconium salt.

[0044] In the present invention, in step (2), there is no special requirement for the usage ratio of the second solvent to UiO-66-NH2. According to a preferred embodiment of the present invention, the usage ratio of the second solvent to UiO-66-NH2 is 5-100 mL solvent / 1.0 g UiO-66-NH2.

[0045] In the present invention, in step (2), there is no special requirement for the usage ratio of the alkylbenzene sulfonic acid to UiO-66-NH2. According to a preferred embodiment of the present invention, the usage ratio of the alkylbenzene sulfonic acid to UiO-66-NH2 is 0.01-1g alkylbenzene sulfonic acid / 1.0g UiO-66-NH2.

[0046] According to a preferred embodiment of the present invention, in step (1): the conditions for the crystallization reaction of solution B include: the reaction temperature is 60-180°C, preferably 80-150°C, and the reaction time is 6-48h, preferably 10-30h.

[0047] According to a preferred embodiment of the present invention, in step (1): the drying is vacuum drying, which is carried out in two stages, preferably the temperature of the first stage is 70-100°C, the time is 1-24h, and the temperature of the second stage is 120-200°C, the time is 1-24h.

[0048] According to a preferred embodiment of the present invention, in step (2): the conditions of the modification treatment include: temperature of 0-40°C and reaction time of 1-8h.

[0049] In the present invention, in step (2), the standing conditions have a wide range of optional ranges. According to a preferred embodiment of the present invention, in step (2): the standing conditions include: a temperature of 0-40°C and a time of 8-24h.

[0050] The invention provides a method for preparing 5-hydroxymethylfurfural, which comprises: in an alcohol solvent and a non-alcohol organic solvent system, in an inert atmosphere, contacting fructose and a catalyst for reaction, and cooling; the catalyst comprises the zirconium-based MOF material.

[0051] In the present invention, the conditions for the contact reaction can be selected in a wide range:

[0052] According to a preferred embodiment of the present invention, the conditions for the contact reaction include: a mass ratio of fructose to catalyst of 1-50:1, preferably 1-20:1.

[0053] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction temperature is 80-200°C, preferably 140-180°C.

[0054] According to a preferred embodiment of the present invention, the conditions of the contact reaction include: the reaction time is 10 min-20 h, preferably 20-100 min.

[0055] According to a preferred embodiment of the present invention, the alcohol solvent is selected from at least one of methanol, ethanol, propanol, n-butanol, isopropanol, isopentanol, ethylene glycol and glycerol, preferably methanol and / or ethanol.

[0056] According to a preferred embodiment of the present invention, the non-alcohol organic solvent is selected from at least one of toluene, cyclohexane, dichloromethane, tetrahydrofuran, acetone and methyl isobutyl ketone.

[0057] According to a preferred embodiment of the present invention, the mass ratio of the alcohol solvent to the non-alcohol organic solvent is 0.05-1, preferably 0.2-1. By adopting the above preferred embodiment, the yield of the product can be further improved.

[0058] The present invention will be described in detail below by way of examples. In the following examples, the raw materials are all commercially available products.

[0059] In the present invention, the reaction product 5-hydroxymethylfurfural is analyzed qualitatively and quantitatively by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of the soluble carbohydrates in the product is analyzed by high performance liquid chromatography (HPLC). The gas chromatography-mass spectrometry instrument is Agilent 7890A of Agilent Corporation of the United States, the chromatographic column is HP-5 non-polar capillary column (30m, 0.53mm), the gas chromatograph is Agilent 7890B, the detector is a hydrogen flame ionization detector (FID), and the chromatographic column is SE-54 capillary column (30m, 0.53mm). The high performance liquid chromatography adopts Agilent 1200 analysis, and the chromatographic column is SHODEX SC1011 sugar column (8×300mm).

[0060] In the present invention, the mass fraction of the S element in the modified MOF material is measured by an inductively coupled plasma atomic emission spectrometer (ICP), model Varian 725-ES, and a physical adsorption instrument model Micromeretic ASAP2020M. The sample is dissolved in hydrofluoric acid to obtain the content of the element. After obtaining the mass fraction of the S element, the -SO3H content is obtained by conversion.

[0061] In the present invention, the XRD measurement method of the modified MOF material is: the phase of the sample is analyzed by using a Rigaku Ultima IV X-ray powder diffractometer from Japan, and a CuKα ray source is used. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.

[0062] In the present invention, the contact angle measuring instrument of the modified MOF material is DSA100 of KRUSS Company of Germany. A tangent line of the gas-liquid interface is drawn from the intersection of the gas, liquid and solid phases, and the angle θ between the tangent line and the solid-liquid boundary line passing through the three-phase contact point is the contact angle of the liquid on the solid surface. When the gas is air, the solid is the modified MOF material, and the liquid is water, the measured contact angle is the contact angle of the modified MOF material with water, wherein the larger the contact angle, the better the relative hydrophobicity of the modified MOF catalyst.

[0063] In the present invention, the scanning electron microscope (SEM) photos of the samples were taken on a Hitachi S-4800II scanning electron microscope. The acceleration voltage of the instrument was 15 kV, and the samples were chrome-plated before analysis.

[0064] In the present invention, the test instrument and test method for the average pore size, specific surface area and pore volume of the sample are: physical adsorption measurement is performed by nitrogen at -196°C using a 3H-2000PM2 physical adsorption instrument to analyze the pore structure characteristics of each adsorption material sample. The initial degassing condition is: degassing operation at 150°C for 6 hours. After measuring the adsorption isotherm of nitrogen on the sample, the specific surface area is calculated using the BET (Brunauer-Emmett-Teller) method, and the pore volume and pore size distribution are calculated using the BJH (Barrett-Joyner-Halenda) method.

[0065] Fructose conversion rate (%) = (molar amount of fructose participating in the reaction) / (molar amount of fructose as the reaction substrate) × 100%.

[0066] The yield of the product 5-hydroxymethylfurfural (%) = (the molar amount of 5-hydroxymethylfurfural produced by the reaction) / (the molar amount of fructose reacted)×100%.

[0067] The selectivity of the product 5-hydroxymethylfurfural (%) = (the molar amount of 5-hydroxymethylfurfural produced by the reaction) / (the molar amount of fructose reacted) × 100%.

[0068] In order to facilitate the understanding of the present invention, the present invention lists the following embodiments, but the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0069] Example 1

[0070] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0071] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0072] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H.

[0073] SEM images of sample UiO-66-NH2-SO3H at different magnifications are shown in Figure 1 As shown, the crystals are uniform cubes with a crystal size of 100-300nm. The -SO3H content of the sample is 1.8wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 77.2°, as shown in Figure 2 shown.

[0074] Example 2

[0075] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 5 mL of acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0076] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0077] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H-2.

[0078] SEM images of sample UiO-66-NH2-SO3H-2 at different magnifications Figure 1 The -SO3H content of the sample is 1.5wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 83.6°.

[0079] Example 3

[0080] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 15 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0081] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0082] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H-3.

[0083] SEM images of sample UiO-66-NH2-SO3H-3 at different magnifications Figure 1 The -SO3H content of the sample is 2.0wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 70.3°.

[0084] Example 4

[0085] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A, and add 10 mL salicylic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0086] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0087] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.1 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H-4.

[0088] SEM images of sample UiO-66-NH2-SO3H-4 at different magnifications Figure 1 The -SO3H content of the sample is 1.9wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 87.5°.

[0089] Example 5

[0090] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0091] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0092] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.3 g of hexadecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.3 g of hexadecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H-5.

[0093] SEM images of sample UiO-66-NH2-SO3H-5 at different magnifications Figure 1 The -SO3H content of the sample is 2.1wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 81.9°.

[0094] Example 6

[0095] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0096] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0097] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.05 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.05 g of dodecylbenzenesulfonic acid, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H-6.

[0098] SEM images of sample UiO-66-NH2-SO3H-6 at different magnifications Figure 1 The -SO3H content of the sample is 1.4wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 68.7°.

[0099] Examples 7-12

[0100] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in the above-mentioned embodiment 1-6, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 160°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 1.

[0101] The gas chromatographic product distribution diagram of the product obtained by catalysis of UiO-66-NH2-SO3H in Example 1 is shown in Figure 3 As shown in the figure, the main product peak HMF peak is higher and more prominent than other peaks, and the product is relatively pure.

[0102] Table 1

[0103]

[0104] Example 13

[0105] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 10g of THF and 10g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0106] Embodiment 14

[0107] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 18g of THF and 2g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0108] Embodiment 15

[0109] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 130°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0110] Example 16

[0111] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 190°C for 30min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0112] Embodiment 17

[0113] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 15min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0114] Embodiment 18

[0115] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of UiO-66-NH2-SO3H in Example 1, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was added to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 120min, and the reaction solution was analyzed to obtain the fructose conversion rate and the yield of the target product 5-hydroxymethylfurfural (HMF), as shown in Table 2.

[0116] In order to more intuitively describe the reaction conditions and results of the above examples, the results of various parameters are listed in Table 2.

[0117] Table 2

[0118] Example Fructose conversion rate (%) HMF yield (%) 13 99.9 76.8 14 80.3 75.7 15 92.3 71.3 16 99.5 68.2 17 90.1 73.9 18 99.8 65.5

[0119] Embodiment 19

[0120] With fructose as substrate, tetrahydrofuran (THF) and isopropanol as solvent, 0.2g of UiO-66-NH2-SO3H of Example 1 above, 0.4g of fructose, 15g of THF and 5g of isopropanol were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 30min, and the reaction solution was analyzed to obtain a fructose conversion rate of 85.5% and a HMF yield of 63.7%.

[0121] Embodiment 20

[0122] With fructose as substrate, tetrahydrofuran (THF) and n-butanol as solvent, 0.2g of UiO-66-NH2-SO3H in the above-mentioned Examples 1-6, 0.4g of fructose, 15g of THF and 5g of n-butanol were added to a stirred autoclave. 0.5MPa of nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to a preset temperature using a programmed heating jacket, and then stirred using a magnetic stirrer. The reaction was carried out at 160°C for 30min, and the reaction solution was analyzed to obtain a fructose conversion rate of 88.1% and a HMF yield of 69.5%.

[0123] Comparative Example 1

[0124] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0125] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0126] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of the above-mentioned UiO-66-NH2, 0.4g of fructose, 15g of THF and 5g of ethanol were added into a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 160°C for 30min, and the fructose conversion rate was 75.3%, and the yield of the target product 5-hydroxymethylfurfural (HMF) was 36.8%.

[0127] The gas chromatographic product distribution diagram of the product obtained by UiO-66-NH2 catalysis is shown in Figure 4 As shown in the figure, the peak height of the main product HMF is significantly lower than that obtained by UiO-66-NH2-SO3H catalysis, and the product purity is lower.

[0128] Comparative Example 2

[0129] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0130] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0131] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of dichloromethane, add 0.1 g of butane sultone, and stir in a water bath at 20°C for 3 h. After standing for one day, separate the product, add 60 mL of dichloromethane and 0.1 g of butane sultone, and stir in a water bath at 20°C for 3 h. After standing for one day, centrifuge the suspension, wash it three times with toluene, and then vacuum dry it at 150°C for 12 h to obtain UiO-66-NH2-SO3H.

[0132] The crystal size of modified UiO-66-NH2 is 150-250nm. The -SO3H content of the sample is 1.4wt%, which is calculated by ICP determination of S content. The contact angle of the sample with water is about 23.2°

[0133] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of the modified UiO-66-NH2, 0.4g of fructose, 15g of THF and 5g of ethanol were added to a stirred autoclave. 0.5MPa of nitrogen was filled to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 160°C for 30min, and the fructose conversion rate was 73.7%, and the yield of the target product 5-hydroxymethylfurfural (HMF) was 49.2%.

[0134] Comparative Example 3

[0135] Weigh 2.0 g zirconium tetrachloride and 1.6 g 2-aminoterephthalic acid and dissolve them in 80 mL N,N-dimethylformamide to obtain solution A. Add 10 mL acetic acid dropwise to solution A at a rate of 0.5 ml / min. Then transfer the system to a crystallization reactor and crystallize at 120° C. for 24 h.

[0136] After crystallization, the mixture was cooled to room temperature, centrifuged to remove the mother liquor, and washed several times with ethanol. The drying was carried out in two stages, the temperature of the first stage was 75°C, the time was 4h, and the drying temperature of the second stage was 180°C, the time was 12h, and UiO-66-NH2 was obtained after vacuum drying.

[0137] Weigh 0.5 g of the prepared UiO-66-NH2, place it in 60 mL of N,N-dimethylformamide, add 0.15 g of polydimethylsiloxane, stir well, place in a 150°C crystallization kettle for reaction for 24 h, centrifuge, wash three times with toluene, and then vacuum dry at 150°C for 12 h to obtain modified UiO-66-NH2.

[0138] The crystal size of modified UiO-66-NH2 is 300-400nm. The sample does not contain SO3H, and the contact angle between the sample and water is about 85.5°

[0139] With fructose as substrate, tetrahydrofuran (THF) and ethanol as solvent, 0.2g of the modified UiO-66-NH2, 0.4g of fructose, 15g of THF and 5g of ethanol were added into a stirred autoclave. 0.5MPa of nitrogen was introduced to prevent the organic solvent from boiling. The temperature was raised to the preset temperature by a programmed heating jacket, and then stirred by magnetic stirring. The reaction was carried out at 160°C for 30min, and the fructose conversion rate was 68.7%, and the yield of the target product 5-hydroxymethylfurfural (HMF) was 28.7%.

[0140] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A zirconium-based MOF material, characterized in that: The contact angle between the zirconium-based MOF material and water is not less than 50°, and the zirconium-based MOF material contains not less than 1.0 wt % of sulfonic acid modified groups.

2. The zirconium-based MOF material according to claim 1, wherein The contact angle between the zirconium-based MOF material and water is 50-120°, preferably 60-100°; and / or The content of sulfonic acid modified groups in the zirconium-based MOF material is 1.0-10.0 wt %, preferably 1.5-6.0 wt %.

3. The zirconium-based MOF material according to claim 1 or 2, wherein: The zirconium-based MOF material has a polyhedral cubic structure, and the size of the material is 50-800 nm, preferably 100-500 nm.

4. A method for preparing the zirconium-based MOF material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step (1), preparing UiO-66-NH2; Step (2), modifying UiO-66-NH2 with alkylbenzene sulfonic acid, separating after standing, and vacuum drying.

5. The preparation method according to claim 4, wherein The alkylbenzenesulfonic acid is a benzenesulfonic acid having a C10-C16 alkyl branch, preferably dodecylbenzenesulfonic acid and / or hexadecylbenzenesulfonic acid.

6. The preparation method according to claim 4 or 5, wherein: The step (1) comprises: dissolving a zirconium salt and 2-aminoterephthalic acid in a first solvent to form a solution A, adding a carboxylic acid compound to the solution A to form a solution B, performing a crystallization reaction, and drying; and / or The step (2) comprises: dissolving UiO-66-NH2 in a second solvent, adding alkylbenzene sulfonic acid for modification, standing and separating, repeating the modification, standing and separating steps at least once, preferably 1-3 times, and vacuum drying; Preferably, The first solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide and triethylamine; and / or The second solvent is selected from at least one of dichloromethane, toluene, tetrahydrofuran, and p-xylene; and / or The carboxylic acid compound includes at least one of formic acid, acetic acid, citric acid, tartaric acid, benzoic acid, salicylic acid, phthalic acid, phenylpropionic acid, phenylacetic acid, succinic acid, and p-nitrobenzoic acid.

7. The preparation method according to claim 6, wherein: In step (1), The molar ratio of the zirconium salt to 2-aminoterephthalic acid is 1:(0.5-3); and / or The ratio of the first solvent to the zirconium salt is 5-100 mL solvent / 1.0 g zirconium salt; and / or The ratio of the carboxylic acid compound to the zirconium salt is 0.01-20 mL of the carboxylic acid compound / 1.0 g of the zirconium salt; In step (2), The ratio of the second solvent to UiO-66-NH2 is 5-100 mL solvent / 1.0 g UiO-66-NH2; and / or The usage ratio of the alkylbenzene sulfonic acid to UiO-66-NH2 is 0.01-1g alkylbenzene sulfonic acid / 1.0g UiO-66-NH2.

8. The preparation method according to claim 6, wherein: In step (1): The conditions for the crystallization reaction of the solution B include: the reaction temperature is 60-180° C., preferably 80-150° C., the reaction time is 6-48 hours, preferably 10-30 hours; and / or The drying is vacuum drying, which is carried out in two stages, preferably the temperature of the first stage is 70-100°C, the time is 1-24h, and the temperature of the second stage is 120-200°C, the time is 1-24h; In the step (2): The modification treatment conditions include: temperature of 0-40°C, reaction time of 1-8h; and / or The standing conditions include: temperature of 0-40°C and time of 8-24h.

9. A method for preparing 5-hydroxymethylfurfural, characterized in that: The preparation method comprises: in an alcohol solvent and a non-alcohol organic solvent system, in an inert atmosphere, contacting fructose and a catalyst for reaction, and cooling; the catalyst comprises the zirconium-based MOF material according to any one of claims 1 to 3; Preferably, The conditions of the contact reaction include: The mass ratio of fructose to catalyst is 1-50:1, preferably 1-20:1; and / or The reaction temperature is 80-200°C, preferably 140-180°C; and / or The reaction time is 10 min-20 h, preferably 20-100 min.

10. The preparation method according to claim 9, wherein: The alcohol solvent is selected from at least one of methanol, ethanol, propanol, n-butanol, isopropanol, isopentanol, ethylene glycol and glycerol, preferably methanol and / or ethanol; and / or The non-alcohol organic solvent is selected from at least one of toluene, cyclohexane, dichloromethane, tetrahydrofuran, acetone, and methyl isobutyl ketone; Preferably, the mass ratio of the alcohol solvent to the non-alcohol organic solvent is 0.05-1, preferably 0.2-1.

Citation Information

Patent Citations

  • Method for generating 5-hydroxymethylfurfural by using ionic liquid catalysis

    CN101812039A

  • Solid acid catalyst for 5-hydroxymethyl furfural synthesis and preparation method thereof

    CN103028424A

  • Preparation and separation method for preparing 5-hydroxymethylfurfural through fructose dehydration

    CN113234043A